2018
DOI: 10.2337/db17-0318
|View full text |Cite
|
Sign up to set email alerts
|

The Diabetes Gene and Wnt Pathway Effector TCF7L2 Regulates Adipocyte Development and Function

Abstract: The gene encoding for transcription factor 7-like 2 () is the strongest type 2 diabetes mellitus (T2DM) candidate gene discovered to date. The TCF7L2 protein is a key transcriptional effector of the Wnt/β-catenin signaling pathway, which is an important developmental pathway that negatively regulates adipogenesis. However, the precise role that TCF7L2 plays in the development and function of adipocytes remains largely unknown. Using a combination of in vitro approaches, we first show that TCF7L2 protein is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
111
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 61 publications
6
111
1
Order By: Relevance
“…Conversely, the recessive and TT vs CC models did not reveal a statistically significant association. A plausible mechanism by which this variant affects insulin secretion in diabetic individuals has been proposed by several studies: dysregulation of GLP‐1‐induced insulin secretion, the differential genotype‐dependent expression of insulin enhancer protein regulated by TCF7L2 for insulin secretion in human pancreatic cells and the variant affect the development of adipocytes, which may lead to insulin resistance . Furthermore, Le Bacquer et al observed increased α‐cell development and reduced β‐cell numbers primarily in larger islet cells in carriers of the TT risk genotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the recessive and TT vs CC models did not reveal a statistically significant association. A plausible mechanism by which this variant affects insulin secretion in diabetic individuals has been proposed by several studies: dysregulation of GLP‐1‐induced insulin secretion, the differential genotype‐dependent expression of insulin enhancer protein regulated by TCF7L2 for insulin secretion in human pancreatic cells and the variant affect the development of adipocytes, which may lead to insulin resistance . Furthermore, Le Bacquer et al observed increased α‐cell development and reduced β‐cell numbers primarily in larger islet cells in carriers of the TT risk genotype.…”
Section: Discussionmentioning
confidence: 99%
“…CI, confidence interval; OR, odds ratio by several studies: dysregulation of GLP-1-induced insulin secretion, the differential genotype-dependent expression of insulin enhancer protein regulated by TCF7L2 for insulin secretion in human pancreatic cells 55 and the variant affect the development of adipocytes, which may lead to insulin resistance. 56 Furthermore, Le Bacquer et al 57 observed increased α-cell development and reduced β-cell numbers primarily in larger islet cells in carriers of the TT risk genotype. Interestingly, increased TCF7L2 expression was detected in the sorted α-cells compared with β-cells of diabetic patients, 58 suggesting that this could be the reason for the increased α-/β-cell ratio in the islet cells.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, transgenic mice over-expressing Tcf7l2 displayed HFD-induced glucose intolerance (14). Contrasting these findings, targeted deletion of Tcf7l2 in mature adipocytes (mADs) resulted in enhanced adiposity, glucose intolerance and hyperinsulinaemia (11,12). In humans, TCF7L2 expression was decreased in the SC abdominal (hereafter referred to as abdominal) AT of subjects with impaired glucose tolerance (11) and reduced systemic insulin sensitivity (15).…”
Section: Introductionmentioning
confidence: 95%
“…Contrasting these findings, targeted deletion of Tcf7l2 in mature adipocytes (mADs) resulted in enhanced adiposity, glucose intolerance and hyperinsulinaemia (11,12). In humans, TCF7L2 expression was decreased in the SC abdominal (hereafter referred to as abdominal) AT of subjects with impaired glucose tolerance (11) and reduced systemic insulin sensitivity (15). Notably, non-coding genetic variation at the TCF7L2 locus was demonstrated to be the strongest genetic determinant of type 2 diabetes (T2D) risk in humans (16,17).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation